Performance Evaluation of Diallyl Disulfide (DADS) as a Soil Urease Inhibitor - MANOGARAN, M.DEVENDRAN (2021)
Urease inhibitors have been introduced as a mitigation approach to reduce nitrogenous loss experienced by urea fertilizer when applied to soil. Diallyl disulfide (DADS) is an organosulfur compound similar to allicin and diallyl trisulfide (DATS) which have been recognized for their urease inhibitory traits attributed to the disulfide bond present in their structure. DADS also constitutes of the disulfide bond hence, it is expected that DADS inhibits urease activity as well. This research aims to optimize DADS’s concentration and duration of inhibition, determine stability of DADS in an enzymesubstrate- inhibitor interaction under different soil conditions and determine the kinetic parameters of soil urease affected by the inhibitory property of DADS as well as categorize the mode and type of inhibition. Colorimetric method was used to optimize DADS’s concentration. High Performance Liquid Chromatography (HPLC) was also employed for quantification of DADS retained in soil under different parameters. The Lineweaver-Burk plot was applied to determine the effect of DADS on the kinetic parameters of urease. The results indicated that 5 % DADS/urea-N (w/w) treatment portrayed the best urea hydrolysis and nitrification inhibition traits on average for seven sampling days, up to 81.82 % and 27.92 % respectively. Under all the different soil conditions tested, DADS experienced deterioration to allow the occurrence of the thioldisulfide interaction to inhibit urease activity. However, when the soil conditions were altered to 20°C, 15 % soil moisture content and pH 4, the concentration of DADS retained was higher up to 10.73 μg, 6.62 μg and 7.94 μg respectively. DADS treatments increased the Km and decreased the Vmax values, hence behaving as a mixed inhibitor. The catalytic capacity index, Vmaz/Km of 5, 8 and 10 % DADS/urea-N (w/w) treatments were 0.8433, 0.7965 and 0.7707 respectively which were all significantly lower in comparison to the control sample which exhibited a Vmax/Km value of 0.9489 further strengthening the potency of DADS as a urease inhibitor. The findings suggest that DADS exhibits immense potential as an environmental friendly urease inhibitor as it is effective at low concentrations, compatible with urea and chemically stable.